Study protocol: the Heart and Brain study - Suri, S; Bulte, D; Chiesa, ST; Ebmeier, KP; Jezzard, P; Rieger, S; Pitt, J; Griffanti, L; Okell, T; Craig, M; Chappell, M; Blockley, N; et al. (Frontiers Media, 2021)
Background: It is well-established that what’s good for the heart is good for the brain; vascular factors such as hypertension, diabetes, and high cholesterol, and genetic factors such as the apolipoprotein E4 allele increase the risk of developing both cardiovascular disease and dementia. However, the mechanisms underlying the heart-brain association remain unclear. Recent evidence suggests that impairments in vascular phenotypes and cerebrovascular reactivity (CVR) may play an important role in cognitive decline. The Heart and Brain Study combines state-of-the-art vascular ultrasound, cerebrovascular magnetic resonance imaging (MRI) and cognitive testing in participants of the long-running Whitehall II Imaging cohort to examine these physiological processes together. This paper describes the study protocol, data pre-processing and overarching objectives.